Political dispute in Poland in the eyes of Facebook slacktivists - Pawlak, Piotr (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2021)
This text is a report from research on selected aspects of the crisis of democracy in Poland. The problem of the analysis focuses on questions about the attitude of the participants in the political dispute towards opponents, the possibility (and method) of reaching an agreement and the assessment of the situation. I chose the area of analysis considering social media a transparent platform for political dispute (especially during the SARS-CoV-2 pandemic). The essence of the research was to find respondents clearly involved in the political dispute. I choose Facebook, among the other things, because this platform creates a place of many actively operating thematic groups which gathers supporters of particular political options. This fact facilitate reaching respondents with the preferred characteristics. The survey was conducted in the period 13/12/2020 to 25/01/2021 on the basis of the author’s form consisting of 15 questions. The research sample consists of 220 respondents: 126 women and 94 men aged 14 to 72 years old. Appropriately for the nature of the variables and the sample size, the contingency coefficient and the Kruskal-Wallis test were calculated, together with the statistical significance of the obtained results. All analyzes were performed on the basis of SPSS software version 26 and Microsoft Excel.

Niniejszy tekst jest raportem z badań nad wybranymi aspektami kryzysu demokracji w Polsce. Problem analizy koncentruje się na pytaniach o stosunek uczestników sporu politycznego do przeciwników, możliwości (i sposobu) osiągnięcia porozumienia oraz oceny sytuacji. Obszar analizy wybrałem, traktując media społecznościowe jako przejrzystą platformę do sporu politycznego (szczególnie podczas pandemii SARS-CoV-2). Istotą badania było znalezienie respondentów wyraźnie zaangażowanych w spór polityczny. Autor wskazał portal Facebook między innymi dlatego, że platforma ta tworzy miejsce dla wielu aktywnie działających grup tematycznych, skupiających zwolenników poszczególnych opcji politycznych. Fakt ten ułatwia dotarcie do respondentów o preferowanych cechach. Badanie przeprowadzono w okresie od 13.12.2020 r. Do 25.01.2021 r. Na podstawie autorskiego formularza składającego się z 15 pytań. Próba badawcza liczy 220 respondentów: 126 kobiet i 94 mężczyzn w wieku od 14 do 72 lat. Odpowiednio do charakteru zmiennych i liczebności próby obliczono współczynnik kontyngencji i test Kruskala-Wallisa oraz istotność statystyczną uzyskanych wyników. Wszystkie analizy wykonano w oparciu o oprogramowanie SPSS w wersji 26 i Microsoft Excel.
Spór polityczny w Polsce, w oczach facebookowych slaktywistów
Keywords: democracy crisis; hate speech; slacktivism; social media; kryzys demokracji; mowa nienawiści; lenistwo; media społecznościowe